Indexing policy in a collaborative environment: an analysis in Brazilian digital libraries of dissertations and thesis - Dal' Evedove Tartarotti, Roberta Cristina [UNESP]; Dal' Evedove, Paula Regina; Lopes Fujita, Mariangela Spotti (Univ Zaragoza, 2018)
One of the challenges in the area of Knowledge Organization and Representation is to follow the dynamics of document treatment in face of the technological and cultural changes experienced in the contemporary world. Considering the importance of indexing policy guidelines for guiding indexing by subjects in digital libraries, the objective of this work was to analyze the presence of indexing policies in collaborative environments, facing the inherent specificities that surround the social indexing performed by users for the thematic representations of documents. Regarding the methodology, an electronic questionnaire was applied to the responsible persons fot the dissertations and thesis digital libraries in Brazil. The results indicate, mainly i , the absence of an indexing policy that supports the practice of indexing in collaborative environments.
Keywords: Indexing policy; Collaborative indexing; Digital libraries; Dissertations and thesis; Brazil